Proceedings of the ACM International Conference on Interactive Tabletops and Surfaces 2009
DOI: 10.1145/1731903.1731912
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of natural gestures for controlling robot teams on multi-touch tabletop surfaces

Abstract: Multi-touch technologies hold much promise for the command and control of mobile robot teams. To improve the ease of learning and usability of these interfaces, we conducted an experiment to determine the gestures that people would naturally use, rather than the gestures they would be instructed to use in a pre-designed system. A set of 26 tasks with differing control needs were presented sequentially on a DiamondTouch to 31 participants. We found that the task of controlling robots exposed unique gesture sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 16 publications
(12 reference statements)
0
25
0
2
Order By: Relevance
“…Such studies have been used to design gesture interfaces of various types including multitouch gestures on small and large surfaces [2,10,11,22,25,32,57] and multi-modal interactions [28]. There is evidence that user-defined gesture sets are more complete than those defined solely by experts [2,32,35,57].…”
Section: User-elicitation Studiesmentioning
confidence: 99%
“…Such studies have been used to design gesture interfaces of various types including multitouch gestures on small and large surfaces [2,10,11,22,25,32,57] and multi-modal interactions [28]. There is evidence that user-defined gesture sets are more complete than those defined solely by experts [2,32,35,57].…”
Section: User-elicitation Studiesmentioning
confidence: 99%
“…We consulted multi-touch device SDKs and user guides (nicely summarized in [31]) and related research [3,5,7,11,16,17,30]. To keep the study reasonable and more ecologically valuable, we selected only gestures which use a single posture (e.g.…”
Section: Gesture Setmentioning
confidence: 99%
“…Wobbrock et al [33] investigated user-defined gestures for general interactions on multi-touch tabletops and found that touchingand-dragging is the most natural method for translating digital objects, and that dragging by the corner is the most natural way to rotate objects. Similarly, Micire et al [19] conducted an analysis of user-defined gestures for robot manipulation on a multi-touch tabletop. They too found that touch dragging was the most used gesture for positioning robots.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, many researchers are investigating their usefulness for completing an increasingly diverse collection of tasks, including: the control of robots [19], the control of systems [8,21], managing artifacts [2,3,13], and software engineering [9]. Most of these systems support the selection and manipulation of digital objects on the screen using direct touch, exploiting the naturalness of physical direct interaction.…”
Section: Introductionmentioning
confidence: 99%